2010
DOI: 10.1080/02640414.2010.487071
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting athletes' body mass index to better reflect adiposity in epidemiological research

Abstract: The aim of the present study was to identify when body mass index (BMI) is unlikely to be a valid measure of adiposity in athletic populations and to propose a simple adjustment that will allow the BMI of athletes to reflect the adiposity normally associated with non-athletic populations. Using data from three previously published studies containing 236 athletes from seven sports and 293 age-matched controls, the association between adiposity (sum of 4 skinfold thicknesses, in millimetres) and BMI was explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 14 publications
2
31
0
2
Order By: Relevance
“…This inability of BMI to assess fatness or adiposity has been reported in the literature [90] . Despite this limitation, the use of MI instead of BMI may permit diagnosis of underweight and assessment of "optimum body weight" for high performance in sports on a finer scale.…”
Section: Body Mass Index (Bmi) and Mass Index (Mi)mentioning
confidence: 96%
“…This inability of BMI to assess fatness or adiposity has been reported in the literature [90] . Despite this limitation, the use of MI instead of BMI may permit diagnosis of underweight and assessment of "optimum body weight" for high performance in sports on a finer scale.…”
Section: Body Mass Index (Bmi) and Mass Index (Mi)mentioning
confidence: 96%
“…The estimated magnitude of this bias in middle-school students is consistent with, but smaller than, the elite athletic bias of more than 20% documented by direct measurement (Nevill et al, 2010). This indirect evidence should be supplemented by studies in which direct measurement of adiposity are compared with BMI and BMI percentile for individuals at various levels of physical activity performance.…”
Section: Discussionmentioning
confidence: 83%
“…This has led coaches and trainers to question the validity of BMI as a measure of health risk among athletes (Riewald, 2008;Wein & Palmer, 2008). Substantial athletic bias in elite athletes has been documented by comparing direct adiposity measures and BMI (Nevill et al, 2010); however, this is the first investigation to examine whether a similar bias occurs in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies on students from selected universities in Warsaw, it was found that in the group with high levels of physical activity, there were only people with normal relative weight. In analyses of body composition in young training people, increased BMI does not indicate an increased fraction of fat in body composition [18], but it is a good predictor of fat in an average population [19]. Probably for this reason, there was no greater relationship between the weight-height proportions and the level of activity of the surveyed students of physical education, whereas this correlation was confirmed in relation to the fraction of fat in body composition (especially in women).…”
Section: Discussionmentioning
confidence: 99%